DIGITAL MEDIA LITERACY AWARENESS ON MOBILE DEVICE SECURITY ISSUES - Khdzir, Nik Zulkarnaen; Ahmed, Shekh Abdullah Al-Musa (Journal of Human Capital Development (JHCD), 2019)
Digital literacy is the set of competencies required for full participation in a knowledge society. It includes knowledge, skills, and behaviors involving the effective use of digital devices such as smartphones, tablets, laptops for purposes of communication, expression, collaboration and advocacy. Along with this expansion came a number of security issues to affect mobile devices. A chance to have a tiny and powerful device that is Internet linked and allows communication from anywhere at any time is alluring as well as a problem for companies. Many individuals who have attached their personal smartphones to corporate networks have found out the hard way the cost of doing so. Specifically, there have been a handful of cases where individuals who attached their own personal devices to a company network had their personal phone wiped and all their data and other information lost that was stored on it. Why did this happen? Simply put, a system administrator sent out a remote wipe command to the device and instructed it to wipe itself of all apps and data to keep it from falling in the wrong hands. Or an administrator may have found the device and did not recognize it, so they wiped it in response. If we have an Android device or have read about the operating system, you may have heard the term “rooting the device.” In a nutshell, this refers to undertaking a process of gaining root access to a device. Typically, this involves running an application or script that grants root access to the user. Once access is granted, the user can do pretty much whatever they want on the system without restriction. However, one of the downsides of this process is that the device is now exposed to greater danger from external threats as well. Moreover, this article focus on how digital devices such as smartphones communication and store information for "media education" that is used to define the process of teaching and learning about media. It is about developing people's critical and creative abilities when it comes to mass media, popular culture and digital media. Since digital media is using smartphone for store information and article also referring how to maintain security of these smartphone data. Keywords: encryption, remoteness, digital affixing signature, trojan horse attacks, malware, social engineering attacks, digital literacy, digital media